2009
DOI: 10.2337/dc08-1529
|View full text |Cite
|
Sign up to set email alerts
|

A−β− Subtype of Ketosis-Prone Diabetes Is Not Predominantly a Monogenic Diabetic Syndrome

Abstract: OBJECTIVE -Ketosis-prone diabetes (KPD) is an emerging syndrome that encompasses several distinct phenotypic subgroups that share a predisposition to diabetic ketoacidosis. We investigated whether the AϪ␤Ϫ subgroup of KPD, characterized by complete insulin dependence, absent ␤-cell functional reserve, lack of islet cell autoantibodies, and strong family history of type 2 diabetes, represents a monogenic form of diabetes.RESEARCH DESIGN AND METHODS -Over 8 years, 37 patients with an AϪ␤Ϫ phenotype were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…The mean HbA 1c of T2DM patients reported in this study is similar to that reported in previous studies9192021. DKA was demonstrated to be associated with increased HbA 1c levels which reflect both fasting and postprandial hyperglycemia24 in T1DM23252627 and T2DM28.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The mean HbA 1c of T2DM patients reported in this study is similar to that reported in previous studies9192021. DKA was demonstrated to be associated with increased HbA 1c levels which reflect both fasting and postprandial hyperglycemia24 in T1DM23252627 and T2DM28.…”
Section: Discussionsupporting
confidence: 88%
“…Several reports have indicated the utility of HbA 1c in predicting the development of diabetic retinopathy and nephropathy15161718. The mean HbA 1c is reported to be higher than 10% in T2DM patients with ketosis9192021. Considering the fact that ketosis is the end result of prolonged uncontrolled diabetes2223, we hypothesized that HbA 1c could be used as a screening tool for ketosis in T2DM patients.…”
mentioning
confidence: 99%
“…In conclusion, KPDM is a complex and heterogeneous disease with environmental and genetic factors influencing pathophysiology and clinical progression significantly (32). Currently, the syndromes of KPDM and its specific complications appear to be increasingly recognized worldwide.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study confirmed that the majority (70%) of the A-β-KPDM patients had no significant causal polymorphisms in either the proximal promoter or coding regions of 7 genes, including glucokinase, HNF1A and HNF1B, pancreatic and duodenal homeobox 1, β2/NeuroD1 and paired box gene 4. The investigators regarded that A-β-KPDM is more likely to not be a predominantly monogenic diabetic syndrome (31,32). The previous study by Louet et al (33) showed that neurogenin-3 variations may influence the pathogenesis of KPDM in West African populations but did not show an association with gender distribution.…”
Section: Genetic Susceptibilitymentioning
confidence: 95%
“…For example, we see lean members of specific ethnic groups with antibody-negative, nonketotic diabetes; we treat patients with childhood-onset, antibody-positive diabetes who become insulin resistant as they age; we do not fully understand why some patients progress rapidly to microvascular and/or macrovascular complications or require aggressive escalation of therapy; and we cannot predict the rate of b-cell failure, the degree of weight loss required to normalize glycemia, or the type of medication best suited for a given patient. Attempts at capturing greater granularity have resulted in the creation of new entities, such as latent autoimmune diabetes in the adult to describe autoimmune diabetes with onset after age 30 (1), and ketosis-prone diabetes to describe antibody-negative diabetes with a ketotic onset but only transient insulin requirements (2,3); however, absent a full understanding of the mechanism and its implications, these subtypes emerge mired in controversy or fail to penetrate clinical care (4,5).…”
mentioning
confidence: 99%